Exploring The World Of Chocolate To Enhance Students’ Knowledge Through Industrial Service To Jungle Gold Bali - Pancane, I Wayan Dikse; Suarjana, I Wayan Gede (PT. Hafasy Dwi Nawasena, 2024)
The National University of Education has launched a flagship initiative to improve the quality of education by organizing industry workshops for students. This is not just an ordinary study activity, but a valuable opportunity for students to broaden their horizons about the world of work and business systems, especially in the chocolate industry. These workshops are held at institutions outside of Undiknas, allowing students to experience first-hand the chocolate production process and utilization strategies. The students are not just observers but are actively involved in every stage of the activity. This gives them an in-depth understanding of the intricacies of the chocolate industry, from production to marketing strategies. By actively participating in the workshop, students were able to hone their industry-relevant skills, enhance their practical skills and expand their professional network. Thus, this activity not only enhances knowledge, but also helps students prepare for the challenges of an increasingly competitive world of work. Thus, this workshop activity to the industry is one of the important steps in supporting the lecture activity program of the National Education University in creating graduates who are ready to compete and contribute to the dynamic world of brown industry.